2020
DOI: 10.5194/acp-20-13131-2020
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Estimating aqueous solubilities and activity coefficients of mono- and <i>α</i>,<i>ω</i>-dicarboxylic acids using COSMO<i>therm</i>

Abstract: Abstract. We have used the COSMOtherm program to estimate activity coefficients and solubilities of mono- and α,ω-dicarboxylic acids and water in binary acid–water systems. The deviation from ideality was found to be larger in the systems containing larger acids than in the systems containing smaller acids. COnductor-like Screening MOdel for Real Solvents (COSMO-RS) underestimates experimental monocarboxylic acid activity coefficients by less than a factor of 2, but experimental water activity coefficients are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Unfortunately, COSMO-RS formalism despite relying on chemical intuition, often fails in determining solubility [ 93 , 128 , 129 , 130 , 131 ] and other physicochemical properties [ 132 , 133 , 134 , 135 ]. Probably in most cases, the major explanation is the insufficient precision of available default parameterization [ 128 , 136 ], which on the other hand, in many cases provides quite an accurate match with measured values [ 56 , 90 , 91 , 137 ]. Fortunately, non-substituted benzamide is a relatively simple molecular system, which seems to be well-described by COSMO-RS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, COSMO-RS formalism despite relying on chemical intuition, often fails in determining solubility [ 93 , 128 , 129 , 130 , 131 ] and other physicochemical properties [ 132 , 133 , 134 , 135 ]. Probably in most cases, the major explanation is the insufficient precision of available default parameterization [ 128 , 136 ], which on the other hand, in many cases provides quite an accurate match with measured values [ 56 , 90 , 91 , 137 ]. Fortunately, non-substituted benzamide is a relatively simple molecular system, which seems to be well-described by COSMO-RS.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, theoretical screening enabling the rational selection of the most promising candidates seems indispensable. Unfortunately, despite great efforts [ 18 , 33 , 40 , 45 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], there is no universal and reliable way of predicting solubility in binary aqueous solutions from the molecular structure. Methods developed for proper back-computations of measured solubility data such as Jouyban-Acree, van’t Hoff-Yaws, Wilson, Apelblat, Buchowski-Ksiazczak and Non-Random Two Liquid (NRTL) are interesting from the thermodynamic interpretation viewpoint [ 45 , 61 , 62 , 63 , 64 ], however rather of limited applicability as screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…COSMO-RS, implemented in the COSMO therm program, 28 has been shown to accurately estimate condensed-phase properties, such as solubilities and activity coefficients, of atmospherically relevant multifunctional compounds and water, if suitable conformer distributions are used in the calculation. [29][30][31] Here, COSMOtherm was used to calculate the phase diagrams of some of the ternary SOA-POA-water mixtures, investigated experimentally by Mahrt et al 5 Additionally, the phase separation behavior was predicted for a large set of SOA-POAwater mixtures with possible SOA constituents (p sat o 10 À5 Pa), as well as POA proxies with relatively high O : C ratios (O : C Z 0.125). The SOA constituents were selected from previous studies that have identified possible oxidation products of a-pinene, D3-carene, cyclohexene and isoprene.…”
Section: Introductionmentioning
confidence: 99%
“…COSMO-RS, implemented in the COSMO therm program, 28 has been shown to accurately estimate condensed-phase properties, such as solubilities and activity coefficients, of atmospherically relevant multifunctional compounds and water, if suitable conformer distributions are used in the calculation. 29–31…”
Section: Introductionmentioning
confidence: 99%